2011 12th Intl. Conf. On Thermal, Mechanical &Amp; Multi-Physics Simulation and Experiments in Microelectronics and Microsystem 2011
DOI: 10.1109/esime.2011.5765771
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of metal degradation in power devices under active cycling conditions

Abstract: Metal degradation has recently received increased attention as a failure mechanism in power devices under active cycling conditions, i.e. under repeated pulsed voltage/current loads [1, 2]. Both electro-thermal and thermo-mechanical simulation are indispensable for understanding this mechanisms. The paper presents experimental and simulation data for a dedicated test structure. A suitable lifetime model has to go beyond a simple Coffin-Manson type model to capture the essential influencing parameters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A temperature dependent elastic-plastic J2 constitutive model with kinematic hardening is employed to model the Copper power metallization. The plastic properties listed in Table 3 are taken from [7], [13]. Perfect adhesion of the interface between the Cu metallization and the Si substrate is assumed.…”
Section: Applicationmentioning
confidence: 99%
“…A temperature dependent elastic-plastic J2 constitutive model with kinematic hardening is employed to model the Copper power metallization. The plastic properties listed in Table 3 are taken from [7], [13]. Perfect adhesion of the interface between the Cu metallization and the Si substrate is assumed.…”
Section: Applicationmentioning
confidence: 99%
“…According to the thickness of our metallization a model with temperature dependent properties was chosen. This model was inspired by [9] and uses a bilinear kinematic hardening to describe the elasto-plastic behavior of the metallization ( Figure 6). A literature study was also done for the properties of the intermetallics.…”
Section: Eqmentioning
confidence: 99%
“…Another mechanism has been shown to induce Al extrusion: the ratcheting [8,9,10]. This ratcheting mechanism occurs because of the CTE mismatch between the Si (2 ppm/K) and the molding compound (~11 ppm/K).…”
Section: Introductionmentioning
confidence: 98%
“…For the Cu material, a bilinear kinematic hardening model was used. The procedure for extracting the temperature dependent material data from the wafer curvature experiments is reported in (Lederer et al, 2010) and the material data for Cu can be found in (Kanert et al, 2011).…”
Section: Fem Model Descriptionmentioning
confidence: 99%